2018
DOI: 10.1287/orsc.2018.1204
|View full text |Cite
|
Sign up to set email alerts
|

Starstruck: How Hiring High-Status Employees Affects Incumbents’ Performance

Abstract: This study investigates the effects of high-status inbound mobility on the performance of incumbents. Leveraging sociological theory on status, we suggest that highstatus newcomers generate only limited knowledge spillovers compared to the resources they drain from incumbents. Building on this mechanism, we formulate our first hypothesis that hiring stars negatively affects incumbents' performance. We argue that this effect is asymmetric across incumbents. Because high-status incumbents can better cope with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 114 publications
(111 reference statements)
2
69
0
Order By: Relevance
“…Research has suggested that working with high‐performing stars increases non‐star performance (cf. Azoulay, Graff Zivin, & Wang, 2010; Oettl, 2012), shown how stars can harm non‐star performance, casting stars as unwilling to share resources, cooperate, or make joint decisions (Groysberg, Polzer, & Elfenbein, 2010; Overbeck, Correll, & Park, 2005; Prato & Ferraro, 2018), and highlighted that the effect of high performers on non‐star performance may be contingent on non‐star attributes (Downes, Crawford, Seibert, Stoverink, & Campbell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that working with high‐performing stars increases non‐star performance (cf. Azoulay, Graff Zivin, & Wang, 2010; Oettl, 2012), shown how stars can harm non‐star performance, casting stars as unwilling to share resources, cooperate, or make joint decisions (Groysberg, Polzer, & Elfenbein, 2010; Overbeck, Correll, & Park, 2005; Prato & Ferraro, 2018), and highlighted that the effect of high performers on non‐star performance may be contingent on non‐star attributes (Downes, Crawford, Seibert, Stoverink, & Campbell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if the performance level of stars seems utterly unachievable to others, non-stars may choose to put little or no effort into closing the performance gap (Brown, 2011). Due to their high, broad status, stars are likely to attract substantial organizational resources, since that is often a central rationale in hiring stars (Prato & Ferraro, 2018). By attracting and controlling key organizational resources (Kehoe & Tzabbar, 2015;Zucker et al, 2002), stars and their respective organizations may discount innovative contributions by other individuals (Asgari & Hunt, 2015).…”
Section: Peer-level Impacts Of Starsmentioning
confidence: 99%
“…This effect is especially toxic if there is a gap between status and quality of the performance (Kim & Kang, 2014;Merton, 1968), since high status actors enjoy access to higher budgets, better resources, and more opportunities for recognition (Asgari & Hunt, 2015;Merton, 1968). Prato and Ferraro (2018) showed that new hires actually have a negative impact on incumbents' performance due to limited knowledge spillovers and a significant drain on incumbent resources. Similarly, Agrawal, McHale, and Oettl (2017) showed that hiring stars negatively impacts the performance of incumbents in unrelated fields.…”
Section: Peer-level Impacts Of Starsmentioning
confidence: 99%
See 2 more Smart Citations